Analisis Perilaku Konsumtif Berdasarkan Pengaruh Konsumsi Islam : Studi Kasus Pada Mahasiswa FEB UB - Fiona Berliana Putri (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Shopee PayLater is a form of fintech that allows users to shop online by delaying payment. However, the use of paylater itself is a problem because the MUI fatwa prohibits paylater because it contains riba in its implementation practices, In the campus environment, one of which is FEB Universitas Brawijaya students, it is undeniable that consumptive behavior is one of the behaviors that are often found. This study aims to analyze the effect of debt understanding, usury understanding, financial literacy, and religiosity on the consumptive behavior of students of the Faculty of Economics and Business, Universitas Brawijaya. The research methodology used in this type of research is descriptive quantitative with multiple linear regression analysis models. The results of this study are that understanding debt and financial literacy affect consumptive behavior, while understanding usury and religiosity do not affect consumptive behavior. The implications of this research are expected to contribute insight into the use of Shopee PayLater on consumptive behavior. In addition, it can also be used by educational institutions and governments in controlling consumptive behavior.